2016
DOI: 10.1039/c6nr05792f
|View full text |Cite
|
Sign up to set email alerts
|

Hcp cobalt nanocrystals with high magnetic anisotropy prepared by easy one-pot synthesis

Abstract: Herein we describe the first synthesis of pure mono-disperse spherical hcp-nanocrystals ferromagnetic at room temperature. Our strategy, based on the simple combination of oleylamine and ClCo(PPh), allows the one-pot synthesis of size-controlled hcp-nanocrystals. The size and shape of the nanocrystals can be tuned by varying the reaction time or the concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 51 publications
5
42
0
Order By: Relevance
“…The estimated values of anisotropy constant for Co@A (fcc) and Co@C (hcp) phases are~28 × 10 4 J/m 3 and~39 × 10 4 J/ m 3 , respectively, which are in good agreement with the earlier reports [32,33]. The anisotropy constant for the Co@B (fcc and hcp) is~37 × 10 4 J/m 3 .…”
Section: Magnetic Measurementssupporting
confidence: 88%
“…The estimated values of anisotropy constant for Co@A (fcc) and Co@C (hcp) phases are~28 × 10 4 J/m 3 and~39 × 10 4 J/ m 3 , respectively, which are in good agreement with the earlier reports [32,33]. The anisotropy constant for the Co@B (fcc and hcp) is~37 × 10 4 J/m 3 .…”
Section: Magnetic Measurementssupporting
confidence: 88%
“…Furthermore, we also find lattice distances between 0.18 nm and 0.21 nm, indicating the presence of pristine Co, which exhibits diffraction features in this range. 43 At room temperature and exposure to ambient air, it has been shown that hcp α-Co (hexagonal, P6 3 /mmc) is preferentially formed. 44 However, the fcc phase β-Co (cubic, Fm 3m) exhibits prominent features in this range as well (see Table S1 in the supplementary material).…”
Section: Resultsmentioning
confidence: 99%
“…25 Moreover, several publications relate the use of hcp Co NPs for magnetisation-based applications due to the requirement of small NPs with high anisotropy at usable temperatures, and hcp Co NPs of varying diameters have already been successfully synthesised. [90][91][92][93][94] As it has been shown that size-dependent effects are not prevalent in changes of the magnetic properties of Co clusters induced by ligand coatings, 41 only the influence of the density of the coating on the magnetisation of the 55-atom icosahedron and 57-atom hcp NPs was considered. Ten different coverages of three ligand functional groups commonly used for biocompatibility (-SH, -COOH, and -NH 2 ) were modelled on the icosahedral NP, increasing from 10% to a full 100% coverage in steps of 10%.…”
Section: Resultsmentioning
confidence: 99%